Disability in Narrative Inquiry: A Case of Methodologically Unusable Data from a Participant with Intellectual Disability - Flynn, Susan (My University, 2024)
This paper considers methodological and ethical implications of qualitative interview data that was deemed unusable for research analytic purposes, where the interviewee had an intellectual disability. Critical disability studies theory is used to reimagine the utility of one case of so-called unusable qualitative data. Excerpts from this qualitative data that came from a pilot study interview of a PhD project are full of possibility for learning. Yet, among conclusions drawn, rhetoric about disability inclusion appears undermined by ableist normativity which is a concept that refers to valuing ableness. Specifically, the problems associated with valuing abled ways of speaking within wider narrative research and scholarship will be the focus.
PUBLISHED
https://dsq-sds.org/index.php/dsq/article/view/8516/8077
Keywords: Narrative, intellectual disability, methodology, challenges, ethics